2018
DOI: 10.1159/000491587
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Growth-Promoting Effect of Oxaliplatin in Excision Repair Cross-Complementation Group 1 Transfected Human Colon Cancer Cells

Abstract: The nucleotide excision repair protein excision repair cross-complementation group 1 (ERCC1) has been repeatedly shown to be involved in the sensitivity of cancer cells to platinum derivatives. In order to better understand this process, we transfected HCT-116 cells with a plasmid encoding ERCC1 and studied their in vitro and in vivo behaviour. No main differences were observed for sensitivity to platinum drugs, DNA repair capacity and clonogenicity in vitro. However, ­ERCC1-transfected HCT-116 cells showed pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…As indicated by the T/C >1 (Figure 8d), oxaliplatin promoted the growth of tumor from 9 th to 18 th days. Although, at this stage, we don't have an explanation for this unclassical behavior, we noted that a similar observation was reported earlier for oxaliplatin in a HCT116 tumor xenograft [33] …”
Section: Resultssupporting
confidence: 77%
“…As indicated by the T/C >1 (Figure 8d), oxaliplatin promoted the growth of tumor from 9 th to 18 th days. Although, at this stage, we don't have an explanation for this unclassical behavior, we noted that a similar observation was reported earlier for oxaliplatin in a HCT116 tumor xenograft [33] …”
Section: Resultssupporting
confidence: 77%
“…Eventually it was discovered that Trop-2 may modulate the effects of certain chemotherapeutic regimens. For example, Jordheim et al have suggested that Trop-2 is potentially involved in a paradoxical growth-promoting effect of oxaliplatin, a platinum-based chemotherapeutic, when administered to a xenograft model of HCT-116 human colon cancer cells 38. Moreover, Zhang et al found that curcumin treatment decreases Trop-2 expression and that downregulation of Trop-2 expression suppressed cell proliferation and mobility and increased apoptosis in bladder cancer cells 39…”
Section: Basic Science Backgroundmentioning
confidence: 99%
“…Human trophoblast cell surface antigen 2 (TROP2), also called tumor-associated calcium signal transduction-2 (TACSTD-2), is a surface glycoprotein encoded by TACSTD that has extracellular domains, a single transmembrane domain, and a short tail [ 4 , 5 ]. TROP2 is overexpressed in many human cancers, including ovarian [ 6 , 7 ], gastric [ 8 , 9 ], colorectal [ 10 ], pancreatic [ 11 ], and laryngeal cancers [ 12 ]. Inhibiting TROP2 expression has shown promise in clinical applications [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%